Health-Related Field-Based Fitness Tests: Normative Values for Italian Primary School Children - Christel Galvani; Fabio Togni; Mariangela Valentina Puci; Matteo Vandoni; Luca Correale; Roberto Codella; Claudio Orizio; Cristina Montomoli; Antonio La Torre; Fabio D’Angelo; Francesco Casolo (Journal of Functional Morphology and Kinesiology)
Background/Objectives: conducting fitness tests in educational settings can lead to advantages for both individuals and groups, beyond just enhancing fitness. With the aim of appropriately interpreting performance, this study was conducted to establish sex- and age-specific percentile normative data for a physical fitness (PF) protocol and to define a compound measure of physical performance. Methods: In this cross-sectional study, a short, feasible, and easy-to-administer test battery was performed for 5106 school children, aged 6–10 years. Gender- and age-specific percentiles for the PF tests were constructed, and a Physical Fitness–Motor Competence Performance Index (PF-MC PI) was calculated according to the percentiles. Results: Boys scored higher in all the PF tests when compared to girls (p < 0.001). There was also a trend towards increased PF levels as the age increased in both genders (p < 0.0001). Correlations between scores on individual test items were moderate to high (r from 0.549 to 0.700), and all individual test item scores significantly correlated with the PF-MC PI (p < 0.0001). Conclusions: the provided percentile values will enable the correct interpretation and monitoring of the fitness status of children and the PF-MC PI can be used for easily rating children’s health-related fitness qualities.